Organic Fertilizers History, Production and Applications - Larramendy, Marcelo; Soloneski, Sonia (IntechOpen, 2019)
This book, Organic Fertilizers - History, Production and Applications, aims to provide an update on research issues related to organic fertilizers, highlighting their importance in sustainable agriculture and the environment. We aimed to compile information from diverse sources into a single volume and to give some real-life examples, extending the appreciation of organic fertilizers that may stimulate new research ideas and trends in relevant fields. The contributions in this field of research are gratefully acknowledged. The publication of this book is of great importance for those researchers, scientists, engineers, teachers, graduate students, agricultural agronomists, farmers and crop producers who can use these different investigations to understand the advantages of using organic fertilizers.